Molecular and cellular effects of temperature in oysters Crassostrea brasiliana exposed to phenanthrene - Lima, Daína (2020)
Exposure of aquatic organisms to polycyclic aromatic hydrocarbons (PAH), such as phenanthrene (PHE), may increase the production of reactive oxygen species (ROS) and cause changes in the biotransformation systems. In addition, changes in water temperature can cause adverse effects in the organisms. Estuarine species, like the oyster Crassostrea brasiliana, can adapt and tolerate temperature variation. To evaluate the influence of temperature on biological responses of C. brasiliana exposed to PHE, oysters were maintained at three temperatures (18, 24 and 32 °C) for 15 days and co-exposed afterwards to 100 μg.L-1 of PHE for 24 and 96 h. Levels of PHE in the water and oyster tissues were determined, respectively after 24 and 96 h. In addition, thermal stress, biotransformation and oxidative stress-related genes were analyzed in oyster gills, together with the activity of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-S-transferases (GST) and levels of lipid peroxidation. Oyster accumulated significant levels of PHE. HSP70-like transcripts were affected by PHE exposure only at 32 °C. Transcript levels of cytochrome P450 isoforms (CYP2-like2 and CYP2AU1) were down-regulated in oysters exposed to PHE for 24 h at 32 °C. GSTΩ-like transcript levels were also down-regulated in the PHE-exposed group at 32 °C. After 96 h, CYP2-like2 transcripts were higher in the PHE exposed groups at 32 °C. Oysters kept at 18 °C showed higher levels of SOD-like transcripts, together with higher GST, GPx and G6PDH activities, associated to lower levels of lipoperoxidation. In general the biological responses evaluated were more affected by temperature, than by co-exposure to PHE.